Quantitative analyses of jaw‐opening muscle activity during the active phase of jaw‐closing muscles in sleep bruxism. (1st October 2019) - Maeda, Masana; Yamaguchi, Taihiko; Mikami, Saki; Yachida, Wataru; Saito, Taishi; Sakuma, Toshimitsu; Nakamura, Hironobu; Saito, Miku; Mizuno, Mariko; Yamada, Kyoko; Satoh, Kaoru
Abstract: Rhythmic masticatory muscle activity (RMMA), which is defined as three or more consecutive phasic bursts, accounts for a large part of sleep bruxism (SB). RMMA is thought to be characterized by co‐contraction, a jaw muscle activity in which jaw‐opening muscles contract during the active phase of jaw‐closing muscles, which is different from that during mastication. However, there has been limited information about co‐contraction. The aim of the present study was to clarify the amplitudes and patterns of jaw‐opening muscle activity during the active phase of jaw‐closing muscles in RMMA. Data from 14 healthy volunteers with bruxism, which was diagnosed by using polysomnographic recording with audio‐video, were analysed. RMMA with electromyographic amplitudes of more than two times the baseline amplitude was selected. From the selected RMMA, burst groups consisting of five or more consecutive phasic bursts, including tonic bursts, were selected for analyses. Electromyographic activities during gum chewing were also recorded before sleeping. The minimum, maximum and average value of the amplitudes of jaw‐opening muscle activity during the active phase of jaw‐closing muscles were calculated. Jaw‐opening muscle activity during the active phase of jaw‐closing muscles in RMMA was closer to the baseline than that in gum chewing. The minimum, maximum and average values of amplitudes of jaw‐opening muscle activity during the phase were significantly smaller than those of gum chewing. Contrary to our hypothesis prior to the study, the obtained results suggested that the pattern of electromyogram activity of jaw‐opening and jaw‐closing muscles in RMMA was not necessarily co‐contraction.